Influence of beet flour on the relationship surface-properties of edible and intelligent films made from native and modified plantain flour - Gutiérrez Carmona, Tomy José (2015)
Different studies have been performed on edible films. However, the surface properties and the relationship with their properties has not been analyzed. Edible films were obtained from native and modified plantain flour, with and without the incorporation of beet flour. Moisture content, stability in acidic or alkaline solutions, thermogravimetric analysis (TGA), X-ray diffraction pattern (XRD), differential scanning calorimetry (DSC), attenuated total reflectance Fourier transform infrared spectroscopy (ATR/FTIR), scanning electron microscopy (SEM), atomic force microscopy (AFM) and color parameters were determined. The systems evaluated with the incorporation of beet flour showed a plasticizer effect, which led to the obtaining of more transparent, smoother and wet films. This also was related with higher transmittance and slightest thermodynamic stability. Similarly, the modified plantain flour by cross-linking with sodium trimetaphosphate, allowed to obtain films transparent, smoother, more plastic and degradable. Considering the results, it was concluded that the minor interaction between the starch-starch chains, allowed to obtain films with lower development of the crystalline phase, which favored the obtaining of films transparent, smoother, more plastic and degradable.